Adequacy of core knowledge and soft skills in the performance of professional employees of real estate firms in Nigeria. Issue 2 (18th April 2017) - Oladokun, Sunday Olarinre; Gbadegesin, Job Taiwo
Abstract : Purpose: Real estate professionals are a vital resource to the property firms and the industry at large. Employees' skills, knowledge and competence contribute in great measure to organization's business performance. The purpose of this paper is to examine the adequacy of core knowledge and soft skills possessed by professional employees within the Nigerian real estate practicing firms. It also assesses the performance of the employees and establishes the correlation among the soft skills possessed by employees. Design/methodology/approach: Data for this study were elicited through the administration of questionnaires on principal partners/branch managers (the employers) of the practicing estate surveying and valuation firms in Lagos metropolis. Data collected were analyzed using descriptive statistics, one-sample t -test and correlation analysis. Findings: The result indicates that employees of estate firms in Nigeria demonstrate adequate knowledge in ten out of 21 core areas of real estate practice, while real estate agency has the highest mean, and inadequate knowledge in six others with least mean score in environmental impact assessment. The study also revealed that employees possess good listening and communication skills but are deficient in courteousness and writing skill, among others. It was also found that real estate employees were performing the best in inspection functions but below average in report writing and handling of transaction. The study also established a significant relationship among all the soft skills except communication skill and courteousness. Research limitations/implications: Further study that looks at the performance of real estate graduates working in other sectors/organizations other than estate companies is required to establish their competence level in global employment market. Further study is also needed to cover the views of the employees in Nigerian market as this study focuses on the views of the employers. Originality/value: This study provides an important feedback for the policy makers in the design/review of curriculum for real estate education towards enhancing employability of the graduates. This study also serves as the research blueprint in giving attention to assessment of soft skills among real estate employees in Nigerian real estate industry.